Miscelánea Studi traduttologici, linguistici e letterari su America Latina e Caraibi - Secci, Maria Cristina (Tertulias, 2019)
Divided into three sections, the volume combines contributions about translation, literature and language in Latin America. "Literature and Translation" is built around the post-1960 generation of authors with forays into the children's genre, "microcuento" and the revision process. "Translation and Culture" delves into literary and publishing history through different translation strategies and in an axis linking Cuba and Italy, while "Language and Dissemination" refers to the dissemination of specialized information and the hybrid discursive genre of digital reviews.